Single Sitting Bilateral Dacryocystorhinostomy for Chronic Dacryocystitis in A Patient with Scleroderma and Bipolar Disorder - Tara Shruthi; Vivek Chaitanya; Preeti Chaudhari; Lakshmi Prabha (Delhi Journal of Ophthalmology)
A 58 years lady presented with chronic pus discharge in both eyes. On examination a diagnosis of bilateral Chronic Dacryocystitis was made. History revealed a psychiatric illness for which she was taking medication. General examination showed aggressive behaviour, thin, shiny & stretched skin over the face with thinned out lips, radial furrowing & glossy appearance of skin around lips causing fish mouth appearance. Other features were taut, hyper pigmented skin over limbs which were highly supportive of dermatologic manifestations of systemic sclerosis. Bilateral Dacryocystorhinostomy with silicone tube intubation under general anesthesia was advised with regard to patient's psychiatric condition and aggressive nature. Procedure was carried out uneventfully. Remarkable healing of wound site was noticed in spite of her skin condition. Here we report a case of bilateral dacryocystorhinostomy done in same sitting in patient with systemic sclerosis which to the best of our knowledge has not been reported.